Betty Crocker vegetarian cooking - Crocker, Betty (John Wiley & Sons, 2012)
"Updated third edition with information on how to fit vegetarianism into a busy lifestyle, how to feed vegetarian kids, and vegetarian myth busters"-- Provided by publisher.